A biocompatible porous Mg-gallate metal–organic framework as an antioxidant carrier. Issue 27 (27th February 2015) - Cooper, Lucy; Hidalgo, Tania; Gorman, Martin; Lozano-Fernández, Tamara; Simón-Vázquez, Rosana; Olivier, Camille; Guillou, Nathalie; Serre, Christian; Martineau, Charlotte; Taulelle, Francis; Damasceno-Borges, Daiane; Maurin, Guillaume; et al.
Abstract : The slow release of gallic acid from a biocompatible porous MOF lead to a strong antioxidant activity. Abstract : A microporous magnesium gallate MOF was prepared from highly biocompatible reagents under environmentally friendly conditions. Its slow degradation in physiological fluids leads to the release of gallic acid and hence a high antioxidant activity, which was illustrated in the HL-60 cell line.